Evaluasi Kinerja Sistem Proteksi Penyulang Trawas PT. PLN (PERSERO) ULP Pandaan - Satria Luthfi Hermawan; Hilman Rangga Nugraha Hermawan; Priya Surya Harijanto; Ahmad Hermawan (Politeknik Negeri Malang, 2024)
The primary objective of this research was to minimize disruptions in the feeder at ULP Pandaan by analyzing the coordination between recloser outgoing and incoming feeders. This study addressed the frequent issue of recloser trips, which caused instability in power supply. The purpose of this research was to provide conclusions and solutions to mitigate these disruptions. The methodology involved a detailed analysis of OCR (Over Current Relay) settings for protective devices on Trawas feeder. This included measurements of primary current settings and TMS (Time Multiplier Setting) values using both standard inverse and normal inverse configurations. Specific settings, such as 25518 A for the Trawas Recloser primary current and a TMS of 0.07, were determined to yield optimal performance. Additional settings for the Outgoing CB (Circuit Breaker) (357061 A, TMS 0.04) and the Incoming CB (181865 A, TMS 1.0) were also established. The important findings revealed that these settings significantly enhanced the reliability of the protective devices, ensuring better coordination between the recloser and CB systems. The implications of this research were substantial, as the optimized settings were expected to reduce the frequency and impact of feeder disruptions. This improvement in system reliability directly benefited both the electricity provider, PT. PLN (Persert), and the consumers by providing a more stable and efficient power supply. In conclusion, this study offered a comprehensive analysis and practical solutions for enhancing the protection system's performance on the Trawas feeder, which could be applied to similar electrical distribution networks to achieve better stability and reliability.